zum Directory-modus

Grundlegende Differenziationsregeln

Beweis der Summenregel

Theorem
Eine Summe von Funktionen kann gliedweise differenziert werden.
f ( x ) = f 1 ( x ) + f 2 ( x ) f ' ( x ) = f 1 ' ( x ) + f 2 ' ( x )
y = lim Δ x 0 f ( x + Δ x ) - f ( x ) Δ x = lim Δ x 0 f 1 ( x + Δ x ) + f 2 ( x + Δ x ) - f 1 ( x ) - f 2 ( x ) Δ x = lim Δ x 0 f 1 ( x + Δ x ) - f 1 ( x ) Δ x + f 2 ( x + Δ x ) - f 2 ( x ) Δ x = lim Δ x 0 f 1 ( x + Δ x ) - f 1 ( x ) Δ x + lim Δ x 0 f 2 ( x + Δ x ) - f 2 ( x ) Δ x = f 1 ' ( x ) + f 2 ' ( x )
Seite 5 von 13